Newspaper advertisements as an indicator of verticalization: A case study of the Eureka Post - Litty, Samantha M. (Bergen Language and Linguistics Studies, 2022)
Comparing advertisements published in both the English and German versions of the Eureka Post, a newspaper from Eureka, South Dakota, this study explores one avenue of potential language shift under the verticalization model and aims to gauge external influences on this one particular community-controlled institution. By assessing advertising language in two parallel publications, external and internal community influences should be visible over time. If external factors are attributing to a shift of the print language from the community-dominant language (which is non-dominant in broader society) to the dominant language, this should be evidenced in an increase of advertisements in the non-dominant community language. However, the results indicate that at a time where verticalization processes are changing the publishing landscape in other areas of the Midwest, in Eureka, South Dakota, the opposite appears to be true. The community-dominant language, German, sees an increase in advertisements published in German and a decrease in those published in English.